Proceso de atención de enfermería en paciente pre - escolar con Neumonía Bacteriana. - Espinoza Olvera, Liz Izamar (2021)
The objective of this case study is based on the nursing care process in a preschool patient with bacterial pneumonia, who attends the emergency area of the Martin Icaza general hospital in the city Babahoyo, due to hyperthermia of 38.5, Chills, tachypnea, accompanied by a productive greenish cough; Bacterial pneumonia, Staphylococcus aureus, Mycobacterium tuberculosis, among others. The application of a nursing care process allows us to provide the necessary nursing care for the correction of altered functional patterns and obtain a favorable evolution, shortly accessing the recovery and rehabilitation of the patient´s health.